The Role of Hybrid Work Arrangements in Enhancing Employee Productivity - Kristanto, Yudha; Mansur, Ahmad (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
This study investigates the role of hybrid work arrangements in enhancing employee productivity at PDAM Kabupaten Semarang Cabang Salatiga, aiming to understand how flexible work models impact work performance and collaboration. Utilizing a qualitative research design, the study collects data through semi-structured interviews with employees, managers, and human resources personnel, along with document analysis to provide a comprehensive understanding of the subject. The findings reveal that hybrid work arrangements improve productivity by offering flexibility, reducing commuting time, and enhancing work-life balance. However, challenges such as communication gaps, collaboration issues, and technological disparities were identified as barriers to optimal productivity. The research highlights the importance of reliable technology, inclusive practices, and support mechanisms to address these challenges. The study's value lies in offering insights into how hybrid work can be optimized for improved employee performance and organizational success, while also contributing original knowledge on the intersection of flexible work models and productivity. The findings have practical implications for organizations considering or already implementing hybrid work models, suggesting strategies for overcoming obstacles and enhancing productivity in hybrid environments